How Effective and Safe Is Bronchial Thermoplasty in "Real Life" Asthmatics Compared to Those Enrolled in Randomized Clinical Trials?. (8th September 2016) - Arrigo, Rita; Failla, Giuseppe; Scichilone, Nicola; La Sala, Alba; Galeone, Carla; Battaglia, Salvatore; Benfante, Alida; Facciolongo, Nicola
Abstract : There is limited information on the efficacy and safety of bronchial thermoplasty (BT) in real life . We evaluated the outcomes of the randomized clinical trials for BT in severe asthmatics, in whom the exclusion criteria were not strictly controlled. A case series of seven asthmatics (M/F: 4/3; age: 54.6 ± 2.9 years) is reported. Subjects had a statistically significant improvement in AQLQ (from a mean of 3.96 ± 1.1 to 4.5 ± 1.2 and 5.5 ± 0.6 after 6 and 12 months of treatment; p = 0.0007 ) and in the ACQ score (from 2.77 ± 0.8 to 1.83 ± 1.2 and 1.5 ± 0.8 after 6 and 12 months; p < 0.001 ). In the year after BT, severe exacerbations, salbutamol use, and OCS use were significantly lower compared with the 1-yr pretreatment period (p < 0.001 ). No ED visits and hospitalization occurred in the year after BT. No changes in functional parameters were recorded. Our investigation confirms the safety and efficacy of BT in severe asthmatics in real life settings.